Shifted-Legendre orthonormal method for delay heat conduction equation. (August 2022) - Mei, Liangcai; Wu, Boying; Lin, Yingzhen
Abstract: In this article, a Shifted-Legendre orthonormal method for solving delay heat conduction equations is considered. This method, based on Legendre orthogonal polynomials, gives the relevant properties of ɛ -optimal approximation solution, and proves the convergence and effectiveness of the constructed numerical algorithm. Numerical examples are given to verify the feasibility of the proposed algorithm.